Cover Picture: Selective Hydrogen Generation from Formic Acid with Well‐Defined Complexes of Ruthenium and Phosphorus–Nitrogen PN3‐Pincer Ligand (Chem. Asian J. 9/2016). Issue 9 (26th April 2016) - Pan, Yupeng; Pan, Cheng‐Ling; Zhang, Yufan; Li, Huaifeng; Min, Shixiong; Guo, Xunmun; Zheng, Bin; Chen, Hailong; Anders, Addison; Lai, Zhiping; Zheng, Junrong; Huang, Kuo‐Wei
Abstract : Formic acid (HCOOH) has been considered as a potential liquid source and storage material for hydrogen. Its high volumetric hydrogen capacity of 53 g H2  L −, equivalent to an energy density of 1.77 kW h L −1, makes it attractive for automotive and mobile applications. A new class of PN 3 ‐pincer complexes were employed for the selective hydrogen generation from HCOOH, and a long life time of 150 h with a turnover number over 1 million was achieved. More information can be found in the Communication by Kuo‐Wei Huang and Junrong Zheng et al. onpage 1357 in Issue 9, 2016 (DOI:10.1002/asia.201600169 ).